2007
DOI: 10.1111/j.1442-9071.2006.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of cigarette smoking on multifocal electroretinogram

Abstract: Cigarette smoking may stimulate the central retinal areas in the acute phase. This effect may be related with the stimulant effect of nicotine on neurotransmission, deleterious effects on retinal and/or choroidal circulation, carbon monoxide toxicity and nicotine withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…We were not able to do macular pigment density measurement in this study; however, normal FTVs in smokers suggest that chronic smoking in adults might not be associated with decreased macular pigment density. Increased FTV immediately after photostress, considering our findings from electrodiagnostic studies [11,12,13] suggests chronic, subclinical toxicity in the macula of chronic smokers. On the other hand, rapid adaptation to photostress may be beneficial in performing duties under glare, such as driving in the night.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We were not able to do macular pigment density measurement in this study; however, normal FTVs in smokers suggest that chronic smoking in adults might not be associated with decreased macular pigment density. Increased FTV immediately after photostress, considering our findings from electrodiagnostic studies [11,12,13] suggests chronic, subclinical toxicity in the macula of chronic smokers. On the other hand, rapid adaptation to photostress may be beneficial in performing duties under glare, such as driving in the night.…”
Section: Discussionmentioning
confidence: 65%
“…We previously showed that acute smoking significantly hastens the latency time from eye to visual cortex [11], and this is associated with abnormalities in the macula detected by pattern electroretinography [12] and multifocal electroretinography [13]. Electrocortical activation shown in the previous studies and decrements in ocular blood flow in the acute phase indicated that this effect is mediated via nicotine’s action on neuronal systems [11,12,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported an increased risk of bilateral advanced AMD in current smokers and heavy smokers. They strongly recommended promotion of smoking cessation advice among general population with particular emphasis on current smokers with unilateral ARMD 5 . Apart from ARMD, cataract which is the other leading cause of severe visual impairment is also accelerated by smoking tobacco 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in recent years that acute exposure to cigarette smoking may stimulate the central retinal areas measured by the increase of P1 amplitudes of multifocal electroretinography (mfERG)4 and have stimulant effects of pattern visual-evoked potentials (PERG) 5. It was speculated that this effect might be related to the stimulant effect of nicotine on neurotransmission, deleterious effects on retinal and/or choroidal circulation, carbon monoxide toxicity and nicotine withdrawal 4…”
Section: Retina and Optic Nerve Functionmentioning
confidence: 99%